Impacts of the Fomento Program on Family Farmers in the Brazilian Semi-Arid and its relevance to climate change: a case study in the region of Sub medio São Francisco - Mesquita, Patrícia; Folhes, Ricardo Theophilo; Cavalcante, Louise; Rodrigues, Luciana Vieira de Novais; Santos, Beatriz Abreu; Rodrigues-Filho, Saulo (Sustainability in Debate, 2020)
For some years, Brazil established itself as a leader in strategies of strategies and programs aimed at reducing the social vulnerability of the most vulnerable populations. In this context, the Program for the Promotion of Rural Productive Activities (Fomento Program), created in 2011, had as one of the main objectives to stimulate the generation of work and income, and promote food and nutritional security for rural, indigenous, traditional and settled populations of agrarian reform. In the Northeast, and more specifically in the Semi-arid region, the relevance of this Program stands out even more concerning climate projections, which indicates that such areas will suffer from more extreme drought in the face of climate change, affecting populations dependent on climate-sensitive activities. Therefore, given the diversity of impacts of the Fomento Program reported in the literature, this article sought to present results on the perception of the Program’s impacts from 24 family farmers, interviewed through qualitative research in four municipalities in the state of Bahia in 2017. In addition to the socio-productive aspects, the research sought to understand the Program’s impacts in the context of climate change. The results point to a positive perception mainly related to changes in production and technical assistance based on the Paradigm of Co-existence with the Semi-arid Region.